KESELARASAN MANAJEMEN BISNIS SYARIAH DENGAN PEMANFAATAN SAMPAH PLASTIK KREATIVITAS PRODUK ECOBRICK DI DESA CIBITUNG WETAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Ujang Buchori Muslim; Hasbi Ash Shiddieqy; Nining Yulia Anggraeni (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
Sharia business management is part of the Islamic economic system. The Islamic economic system itself is a system that operates based on the corridors of Islamic values ​​and principles by referring to the Qur'an and Sunnah as guidelines. These values ​​and principles are applied in relation to Allah Subhanahu wa Ta''ala, humans and the environment. With that framework in mind, of course plastic waste is part of the environment, and in its development it is considered a source of environmental damage to ecosystems, its utilization needs to be addressed within the framework of its alignment with sharia business management. Besides being able to pollute the environment, plastic waste can also threaten natural disasters, such as floods. To empower plastic waste into something that can be used, you can even make a profit by making ecobrick products. Ecobrick is a way of processing plastic waste by recycling waste without destroying it. It is in this case that the alignment of sharia business management with ecobrick is introduced, and it is hoped that it will trigger the people of Cibitung Wetan Village to utilize plastic waste into a product that is useful and beneficial to earn income with high selling value.